PENGEMBANGAN MEDIA KOMIK STRIP MENGGUNAKAN APLIKASI IBIS PAIN X UNTUK PEMBELAJARAN TEKS ANEKDOT DI KELAS X ANIMASI SMK NEGERI 04 SEMARANG - Nafiis Syahmi Al Zuhri; Ngatmini (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
This research was conducted with the aim of developing comic strip media in Indonesian language learning using anecdotal text material in class X Animation at SMK Negeri 04 Semarang. The comic strip media developed can be used to support the learning process so that it can make it easier for educators to present lesson material in an interesting way. This research was carried out through stages based on the ADDIE (Analysis, Design, Development, Implementation, Evaluation) development model, including 5 stages, namely, (1) analysis stage, (2) design stage, (3) development stage, (4) implementation stage or trial, (5) evaluation stage. This comic strip media was developed through the Ibis Pain The media that has been developed is tested for feasibility based on the responses of students in class X Animation at SMK Negeri 04 Semarang, a total of 36 students. The results of this research are in the form of comic strip media, anecdotal text material which has been developed using the Ibis Pain the percentage is 91.6% (very feasible), and the final feasibility result by the subject teacher validator is 30 from the ideal score of 32 with a percentage of 93.7% (very feasible). At the implementation stage, the average assessment results obtained based on the responses of trial students were 9.1 out of an ideal score of 10 with a percentage of 91% (very positive). Thus, it can be said that the comic strip media using the Ibis Pain X